1997
DOI: 10.1063/1.474719
|View full text |Cite
|
Sign up to set email alerts
|

Oscillating phase separation in microemulsions. I. Experimental observation

Abstract: We examine the phase separation of a single phase of water-in-oil microemulsion droplets towards a phase of smaller water droplets coexisting with a water-rich excess phase. This transition is found to oscillate when induced by a continuous temperature increase. A periodic clouding and clearing is observed under the microscope and in the microcalorimeter, allowing to determine the oscillation period from the extinction of transmitted light and from the specific heat. The period depends on the surfactant concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 29 publications
5
43
0
Order By: Relevance
“…Many other important areas have bene"ted from nonlinear dynamical approaches. Others that o!er the prospect of reward in this way include the recent reports of oscillatory kinetics accompanying phase transitions in complex #uids (Vollmer, Strey & Vollmer, 1997) and in catalytic reactions under industrial operating conditions (Hadden, Sakakini, Tabatabaei & Waugh, 1997;Werner, Herein, Schultz, Wild & Schlogl, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Many other important areas have bene"ted from nonlinear dynamical approaches. Others that o!er the prospect of reward in this way include the recent reports of oscillatory kinetics accompanying phase transitions in complex #uids (Vollmer, Strey & Vollmer, 1997) and in catalytic reactions under industrial operating conditions (Hadden, Sakakini, Tabatabaei & Waugh, 1997;Werner, Herein, Schultz, Wild & Schlogl, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…For systems containing strong surfactants the interfacial models passed this test surprisingly well: For intermediate surfactant concentrations they provide an accurate description of significant regions of the phase diagrams, as well as of caloric effects related to crossing phase boundaries. Close to the emulsification boundary, where the droplets in a droplet-phase microemulsion start to shrink on expense of forming a coexisting phase containing predominantly the interior of the droplets, the simplest mean-field picture, i.e., a description that neglects all entropic corrections to the Helfrich energy, turned out to yield already an accurate description of thermodynamic properties and of the non-trivial (oscillatory) kinetics of phase separation under constant heating [20].…”
Section: Introductionmentioning
confidence: 98%
“…One of the important achievements was the modeling of static and dynamic properties of membrane and vesicle configurations [2], and of structural phase transitions in amphiphilic mixtures [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. Early work (cf.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the choice of the microstructure sensitively depends on the composition of the samples, and on external control parameters, such as temperature, added salt, alcohol, or dye. For instance a gradual change of the temperature by less then 20°C can lead to a succession of more than four phase transitions between phases with strikingly different macroscopic properties [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%